FORMS OF TAX CONTROL: TAX MONITORING AS A MODERN FORM OF TAX CONTROL - Dolgobaeva D. A. (Relevant issues of management, economics and economic security, 2019)
the article discusses the theoretical aspects of tax control. The main forms of tax control are listed, applicable in Russia. The features of tax monitoring, as a new form of state control, are analyzed. Its advantages in comparison with other forms of tax control are highlighted.
Keywords: налоговая политика; налоговый контроль; налоговая система; налоговый мониторинг; налогоплательщики; tax control; tax policy; tax system; tax monitoring; taxpayers